Hybridization of Banteng (Bos javanicus) and Zebu (Bos indicus) revealed by mitochondrial DNA, satellite DNA, AFLP and microsatellites - Nijman, I.J.; Otsen, M.; Verkaar, E.L.C.; Ruijter, C. de; Hanekamp, E.; Ochieng, J.W.; Shamshad, S.; Rege, J.E.O.; Hanotte, Olivier H.; Barwegen, M.W.; Sulawati, T.; Lenstra, J.A. (Springer, 2003)
Hybridization between wild and domestic bovine species occurs worldwide either spontaneously or by organized crossing. We have analysed hybridization of banteng (Bos javanicus) and zebu (Bos indicus) in south-east Asian cattle using mitochondrial DNA (PCR-RFLP and sequencing), AFLP, satellite fragment length polymorphisms (SFLP or PCR-RFLP of satellite DNA) and microsatellite genotyping. The Indonesian Madura zebu breed is reputed to be of hybrid zebu-banteng origin, but this has never been documented and Bali cattle are considered to be a domesticated form of banteng. The banteng mitochondrial type was found in all animals sampled on the isle of Bali, Indonesia, but only in 35% of the animals from a Malaysian Bali-cattle population. The Madura animals also carried mitochondrial DNA of either zebu and banteng origin. In both populations, zebu introgression was confirmed by AFLP and SFLMicrosatellite analysis of the Malaysian Bali population revealed for 12 out of 15 loci screened, Bali-cattle-specific alleles, several of which were also found in wild banteng animals. The tools we have described are suitable for the detection of species in introgression studies, which are essential for the genetic description of local breeds and the preservation of their economic and cultural value.